1995
DOI: 10.1016/0014-5793(95)00200-s
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of primer tRNALys3 with the p51 subunit of human immunodeficiency virus type 1 reverse transcriptase: a possible role in enzyme activation

Abstract: In the interaction between HIV-1 RT and tRNA Lys3 each subunit of the heterodimer interacts with tRNA showing a different affinity: Kd (p66) = 23 nM, Kd (pS1) = 140 nM. Preincubation of heterodimeric RT with tRNA, at concentrations similar to that of the Kd value for p51, leads to an increase of the catalytic activity on poly(A)-oligo(dT). These results were compared to those using different tRNA analogs: oxidized tRNA, tRNAs lacking one, two or three nucleotides from the 3'-end, or ribo-and deoxyribonucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…We have also shown that the preincubation of HIV-1 RT (either the homodimer p66/p66 [16] or the heterodimer p66/p51 [10]) with tRNA Ly~' 3 led to conformational changes of the enzyme that increases its activity when the assay was performed with the classical poly(A)-oligo(dT) primer-template duplex. [3H]dTTP was used both as primer and as nucleotide precursor.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have also shown that the preincubation of HIV-1 RT (either the homodimer p66/p66 [16] or the heterodimer p66/p51 [10]) with tRNA Ly~' 3 led to conformational changes of the enzyme that increases its activity when the assay was performed with the classical poly(A)-oligo(dT) primer-template duplex. [3H]dTTP was used both as primer and as nucleotide precursor.…”
Section: Resultsmentioning
confidence: 99%
“…We have already described that the maximal activation of HIV-1 RT by tRNA LyS' 3 takes place at concentrations oftRNA allowing each subunit of the p66/p51 HIVol RT to form a complex with tRNA Lys' 3 [10]. The next step was to determine, in the presence of tRNA, the concentration of each compound allowing optimal activation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The stoichiometry and Kd values of the reverse transcriptase and tRNA'2y'' complex formation have been estimated from a Scatchard plot using spectrofluorometric titration data. The p66/p51 heterodimer binds two molecules of tRNA with different affinities (Zakharova et al, 1995a).…”
Section: Dejniiionmentioning
confidence: 99%